The effect of sustainability report disclosure on corporate financial performance with external assurance as moderation - Naibaho, Eduard Ary Binsar; Nabilah, Silvia Gema (Journal of Accounting and Investment, 2025)
Research aims: This study examines does sustainability report disclosure and external assurance affect Indonesian publicly listed enterprises' financial performance. This study analyses how external assurance moderates sustainability disclosure and business financial performance.Design/Methodology/Approach: This quantitative analysis uses 71 Indonesia Stock Exchange-listed non-financial companies over 5 years. Financial records, company sustainability reports, and the Indonesia Stock Exchange database gave five years of data. Sustainability report disclosure and business financial performance were examined using multiple linear regression with external assurance as a moderating variable.Research findings: Economic and social disclosures in sustainability reports improve firm financial performance. External assurance improves financial outcomes directly and supports the favorable influence of sustainability disclosures on corporate performance. These findings demonstrate the strategic importance of transparent and validated sustainability reporting for financial success.Theoretical contribution/Originality: Results demonstrate that external assurance boosts sustainability disclosure and financial success. Credible reporting supports stakeholder theory by meeting expectations and building trust. It supports legitimacy theory, which says assurance fosters company social norms. Signaling theory says external assurance indicates to investors that the firm is transparent, improving its credibility.Practitioner/Policy implication: According to the findings, practitioners should use external assurance in sustainability reporting to promote transparency, stakeholder trust, and financial performance. According to theory, credible and externally confirmed disclosures boost business sustainability efforts. To encourage accountable and trustworthy corporate reporting, policymakers could incentivize or mandate external assurance.Research limitation/Implication: The study only covers Indonesian companies; thus, future research should expand or add qualitative perspectives to acquire deeper insights.